Evaluation of the Periodontal Status in Acromegalic Patients: A Comparative Study. (6th December 2012) - Harb, Ali N.; Holtfreter, Birte; Friedrich, Nele; Wallaschofski, Henri; Nauck, Matthias; Kocher, Thomas
Abstract : Aim . The aim was to compare the periodontal status of the acromegalic patients with healthy subjects from a large population-based cohort (Study of Health in Pomerania, SHIP). Materials and Methods . We studied 32 acromegalic patients (16 females) and 128 randomly selected SHIP subjects (controls) using a 1 : 4 matching. Serum IGF-I and IGFBP-3 levels were measured using the Immulite 2500 system. Periodontitis was assessed by clinical attachment loss (CAL), probing depth (PD), and number of missing teeth. Linear and logistic regression models were used to assess differences in periodontal variables between acromegalic patients and controls. Results . IGF-I levels were comparable in acromegalic patients and controls, whereas IGFBP-3 levels were significantly higher in acromegalic patients (P = 0.004 ). In multivariate modelling, both groups did not differ significantly with respect to mean CAL (P = 0.12 ) and high tooth loss (P = 0.36 ). Mean PD was higher in acromegalic patients by trend (B = 0.28 (−0.00; 0.56)). Conclusion . In acromegalic patients, periodontal disease severity did not differ from their healthy SHIP controls.